Toward indigenous development lessons from the Korean experience [review of] - Tapales, Proserpina D. (1982)
A review of In-Joung Whang, Management of Rural Change in Korea: The Saemaul Undong (Seoul: Seoul University Press, 1981), xviii + 287 pp.
Keywords: Book reviews